Kobaš Walked Circle-Dance – Contributions to the Study of the Slavonian Intangible Cultural Heritage - BERBIĆ KOLAR, Emina; JAGODAR, Josip (Anafora, 2023)
The paper shows the cultural and identity significance of the walked circle-dance of the Posavina village of Slavonski Kobaš, namely: the “slowl” and the “quick” circle-dance as part of the intangible cultural heritage and tradition of the Croatian people. The šetana walked circle-dances, have been protected as intangible cultural property since 2009. Specifically, the Drežnica walked circle-dances are protected, and the subject of this paper are the Kobaš walked circle-dances, which belong to the same geographical and cultural circle as the Drežnica dances. The walked circle-dances are an important element of the cultural identity of the Šokac culture and identity. The aim of the paper is to contribute to the study of walked circle-dances, which are unjustifiably neglected in scientific and professional circles. The significance of walked circle-dances is extremely large in cultural, ethnological, linguistic and literary historical contexts and suggests the possibility of studying the layers of these dances as templates for interpreting history, oral literature, the language of the time in which they originated, ethnology, identity, and generally the cultural understanding of the peoples to whom they are bound as part of the cultural heritage and identity of one locality. The work is based on the methods of field material collection (texts of walked circle-dances), analysing and systemizing the collected material and working on the available archival material. Finally, ecommendations are made for possible further research.